Kinetic and Mechanistic Study of the Oxidation of D-Galactose by Tetraethylammonium Chlorochromate in Aqueous Acetic Acid Medium - Tomar, Ashish; Kumar, Arun (Asian Journal of Chemistry, 2010)
In an attempt to develop new oxochromium(VI) reagents for effective and selective oxidation of organic substrates under mild conditions, the oxidation kinetics of D-galactose with tetraethylammonium chlorochromate (C2H5)4NcrO3Cl has been studied in aqueous acetic acid medium 50% (v/v) in the presence of perchloric acid at constant ionic strength. The reaction, under pseudo-first order condition, is first order with respect to both the [oxidant] and the [substrate]. The reaction is markedly catalyzed by [H+] and the effect of [NaClO4] is negligible. Increasing the dielectric constant of medium decreases the reaction rate. A 1 : 1 stoichiometry is observed and the reaction did not induce the polymerization of acrylonitrile. The reaction has been carried out at different temperatures and the various activation parameters have been computed.